2021
DOI: 10.1186/s12873-021-00427-1
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from reviewing a hospital’s disaster response to the hydrofluoric acid leak in Gumi city in 2012

Abstract: Background This study analyzed the characteristics of hydrogen fluoride-exposed patients (HFEPs) treated in the emergency department (ED) of a local university hospital, and reviewed the hospital’s disaster response according to space, staff, supplies, and systems (4Ss). Methods This retrospective observational chart review and descriptive study included 199 HFEPs among 2588 total ED patients who visited a local university emergency medical center … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In an exclusive study conducted in Gumi City, the Republic of Korea, the issues identified therein include conceptual clarity for preparedness, mitigation, response and rehabilitation, and reconstruction cyclically through detailed analysis of requirements in a hospital setting for minimizing the risk through assessment of manpower, skill, knowledge, experience, expertise, vulnerability, capacity, and inbuilt systems towards disaster response. There has been stress on the felt need of having an overall control network for cohesive actions by the administration, management, and facility (41)…”
Section: Discussionmentioning
confidence: 99%
“…In an exclusive study conducted in Gumi City, the Republic of Korea, the issues identified therein include conceptual clarity for preparedness, mitigation, response and rehabilitation, and reconstruction cyclically through detailed analysis of requirements in a hospital setting for minimizing the risk through assessment of manpower, skill, knowledge, experience, expertise, vulnerability, capacity, and inbuilt systems towards disaster response. There has been stress on the felt need of having an overall control network for cohesive actions by the administration, management, and facility (41)…”
Section: Discussionmentioning
confidence: 99%